Wound-Healing Promotion and Anti-Inflammatory Properties of Carvacrol Prodrugs/Hyaluronic Acid Formulations - Lisa Marinelli; Ivana Cacciatore; Erica Costantini; Marilisa Pia Dimmito; Federica Serra; Antonio Di Stefano; Marcella Reale (MDPI AG, 2022)
Background. Wound healing (WH) is a complex process involving several stages, such as hemostasis, inflammation, re-epithelialization, and remodeling. Many factors can impair WH, and different pharmacological approaches were studied to date, but the increase in antibiotic resistance, invasiveness, treatment duration, and high cost, have often hampered the resolution of the wound. In this study, we investigated the possible application of water-soluble carvacrol prodrugs (WSCPs) and hyaluronic acid (HA) and their formulations (WSCPs/HA) to improve WH and regulate the inflammatory response. Materials and methods. Firstly, the cytotoxicity of 0.1, 1 and 10 µg/mL of HA, WSCPs and WSCPs/HA formulations were evaluated on HaCaT cells and THP-1 cell lines. The ability of WSCPs/HA formulations to modulate wound repair was evaluated in an in vitro model of WH, using HaCaT cells at 6, 18, and 24 h. The expression of WH mediators, after wound closure was determined by qRT-PCR. Following, we polarized THP-1 cells in M1/M2-like macrophages and tested the anti-inflammatory properties of WSCPs/HA formulations. After, we tested the in vitro WH model for the effects of conditioned medium (CM) from M1/M2-like cells cultured in the presence of WSCPs/HA. Results. Results showed that WSCPs/HA formulations were able to significantly raise the wound closure rate, compared to the single constituents, promoting a complete wound closure after 18 h for WSCP1/HA (10 µg/mL) and after 24 h for WSCP2/HA (10 µg/mL), modulating the MMPs, TGFβ, and COX-2 gene expression. The effects of CM derived from M1/M2 polarized cells cultured in the presence of WSCPs/HA determined WH regulation, with a better ability of the WSCP2/HA formulation to modulate the time-dependent expression of reparative and inflammatory mediators. Conclusion. Our data underline the possible application of WSCPs/HA formulations as bioactive agents for the regulation of the wound repair process by the modulation of inflammatory and remodeling phases, affecting the activity of immune cells.